2004
DOI: 10.1016/j.pain.2004.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Control of inflammatory pain by chemokine-mediated recruitment of opioid-containing polymorphonuclear cells

Abstract: Opioid-containing leukocytes can counteract inflammatory hyperalgesia. Under stress or after local injection of corticotropin releasing factor (CRF), opioid peptides are released from leukocytes, bind to opioid receptors on peripheral sensory neurons and mediate antinociception. Since polymorphonuclear cells (PMN) are the predominant opioid-containing leukocyte subpopulation in early inflammation, we hypothesized that PMN and their recruitment by chemokines are important for peripheral opioid-mediated antinoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 61 publications
3
113
3
1
Order By: Relevance
“…Many of these studies used myeloperoxidase activity as a surrogate for neutrophil infiltration, even though flow cytometry provides a more accurate picture of the presence/absence of these cells. Intraplantar injection of chemokines has also been used to recruit neutrophils into the hind paw, but this might result in a different activation state of the cells than that caused by CFA or an incisional wound (56,59).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies used myeloperoxidase activity as a surrogate for neutrophil infiltration, even though flow cytometry provides a more accurate picture of the presence/absence of these cells. Intraplantar injection of chemokines has also been used to recruit neutrophils into the hind paw, but this might result in a different activation state of the cells than that caused by CFA or an incisional wound (56,59).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking selectins, ICAM-1, integrins ␣ 4 and ␤ 2 , or chemokines CXCL1 and CXCL2/3 in vivo substantially decreased opioid-producing immune cells in inflamed tissue or injured nerves (Machelska et al, 1998(Machelska et al, , 2004Brack et al, 2004c;Labuz et al, 2009). In addition, the recruitment of opioid-containing cells is dependent on neurokinin-1 receptors (which bind substance P) (Rittner et al, 2007b), on sensory and sympathetic neurons (Kager et al, 2010), and may be regulated by adhesion to neurons (Hua et al, 2006).…”
Section: Migration Of Opioid Peptide-producing Cells Tomentioning
confidence: 98%
“…In inflamed rat paws it was shown that L-selectin, integrin ␤ 2 , and the CXC chemokine receptor 2 (CXCR2) are coexpressed by opioid peptide-containing leukocytes (Mousa et al, 2000;Brack et al, 2004c;Machelska et al, 2004). Blocking selectins, ICAM-1, integrins ␣ 4 and ␤ 2 , or chemokines CXCL1 and CXCL2/3 in vivo substantially decreased opioid-producing immune cells in inflamed tissue or injured nerves (Machelska et al, 1998(Machelska et al, , 2004Brack et al, 2004c;Labuz et al, 2009).…”
Section: Migration Of Opioid Peptide-producing Cells Tomentioning
confidence: 99%
See 2 more Smart Citations